2020
DOI: 10.1186/s12913-020-05472-3
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic anticipation to reduce emergency department length of stay: a retrospective cohort study in Ferrara University hospital, Italy

Abstract: Background: Emergency Department (ED) crowding reduces staff satisfaction and healthcare quality and safety, which in turn increase costs. Despite a number of proposed solutions, ED length of stay (LOS)-a main cause of overcrowding-remains a major issue worldwide. This retrospective cohort study was aimed at evaluating the effectiveness on ED LOS of a procedure called "Diagnostic Anticipation" (DA), which consisted in anticipating the ordering of blood tests by nurses, at triage, following a diagnostic algorit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
(25 reference statements)
1
0
0
Order By: Relevance
“…According to this study, crowding is significantly associated with prolonged EDLOS. This result is consistent with the study conducted in Sweden [ 47 ], Norway [ 40 ], USA [ 74 ], Italy [ 75 ], and Southern Ethiopia [ 8 ]. Many studies showed that crowding is a global challenge that affects emergency health care services and prolong EDLOS.…”
Section: Discussionsupporting
confidence: 92%
“…According to this study, crowding is significantly associated with prolonged EDLOS. This result is consistent with the study conducted in Sweden [ 47 ], Norway [ 40 ], USA [ 74 ], Italy [ 75 ], and Southern Ethiopia [ 8 ]. Many studies showed that crowding is a global challenge that affects emergency health care services and prolong EDLOS.…”
Section: Discussionsupporting
confidence: 92%